2001
DOI: 10.1074/jbc.m105308200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Novel Mammalian Neuropeptide FF-like Peptides That Attenuate Morphine-induced Antinociception

Abstract: The two mammalian neuropeptides NPFF and NPAF have been shown to have important roles in nociception, anxiety, learning and memory, and cardiovascular reflex. Two receptors (FF1 and FF2) have been molecularly identified for NPFF and NPAF. We have now characterized a novel gene designated NPVF that encodes two neuropeptides highly similar to NPFF. NPVF mRNA was detected specifically in a region between the dorsomedial and ventromedial hypothalamic nuclei. NPVFderived peptides displayed higher affinity for FF1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
301
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(318 citation statements)
references
References 39 publications
9
301
1
Order By: Relevance
“…1), similar to that reported for the human-or rat-cloned NPFF-R2 (14,16,34,35), and that both NPFF-R1 and NPFF-R2 mRNAs were expressed in 3T3-L1 adipocytes (Fig. 2).…”
Section: Discussionsupporting
confidence: 71%
“…1), similar to that reported for the human-or rat-cloned NPFF-R2 (14,16,34,35), and that both NPFF-R1 and NPFF-R2 mRNAs were expressed in 3T3-L1 adipocytes (Fig. 2).…”
Section: Discussionsupporting
confidence: 71%
“…NPSF has almost equal affinity for GPR74 and GPR147, whereas NPFF has at least 10 times higher affinity for the former receptor. 10,13,14 Our results suggest that the two receptors mediate different effects on lipolysis. NPFF has no effect on catecholamineinduced lipolysis using the natural ligand noradrenaline alone.…”
Section: Discussionmentioning
confidence: 62%
“…Detailed examinations of signal transduction can only be carried out in cell systems with stable manipulation of the expression of either or both of the receptors. [5][6][7][8][9]13,14 Unfortunately at present it is not possible to carry out such studies in human adipocytes kept in primary culture. We therefore used an indirect approach by comparing the effect of NPFF with that of NPSF and by using selective lipolysis agents acting on defined steps in signal transduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have been identified primarily by bulk purification from neuroendocrine tissues (10 -12). Additionally, an examination of cleavage sites within the precursors for endogenous peptides showed that nonclassical processing is required to release the peptide from its precursor (13)(14)(15). Finally, mass spectrometric techniques to identify neuropeptides in the brains of mice lacking specific processing enzymes such as CPE have led to the identification of products of nonclassical cleavages (16).…”
mentioning
confidence: 99%